Feminist judgments: interrogating Zimbabwean judgments using anti-essentialist feminist legal theory - Matamba, Rumbidzai (Department of Public Law, 2025)
In 2004, the first feminist judgments project was launched by a group of Canadian lawyers and scholars. This group, calling themselves the Women's Court of Canada, published a series of six rewritten opinions of the Canadian Supreme Court interpreting the Canadian Charter of Rights and Freedoms from a feminist perspective. This model of rewriting original court opinions from a feminist perspective sparked the feminist judgments movement and has been taken up by feminist lawyers and scholars across the globe; in England, Ireland, Australia, the United States, India, New Zealand, South Africa, and Mexico, rewriting significant cases on an array of topics including criminal law, family law, international law, and constitutional law. In each of these projects, feminist scholars and lawyers apply their chosen strands of feminist legal theory to already decided cases to show the practical utility of feminist legal theory to a set of existing facts and laws. Loosely following on this model of rewriting existing judgments from a feminist perspective, this thesis offers commentary on how three Zimbabwean appeal judgments, selected from a reading and review of some of the most prominent cases in the last 20 years, could have been decided differently from an anti-essentialist feminist perspective. The three cases cover the following topics: matrimonial property rights, child custody rights and abortion rights. This commentary is offered as part of the exercise by feminist scholars around the world to put feminist legal theory into practice and to discuss the difference these differently decided judgments would have on women in Zimbabwe, the affected parties in each of the selected cases, and the Zimbabwean society at large. Beginning with a discussion on the development of feminist legal theory in courts, mainly starting in the United States before trickling down to other parts of the world, the thesis focuses on how the three selected judgments, retaining the same facts and legal principles they have been previously decided on, would be altered or bolstered using an anti-essentialist feminist legal theory interpretation. This commentary is followed by a concluding section commenting on the value of feminist legal theory to the Zimbabwean judicial system.